A novel gain-of-function mutation in transient receptor potential C6 that causes podocytes injury: TRPC6 mutation causes podocyte injury - Yu, Min; Hu, Jian; Ju, Tao; Wang, Ren; Wang, Meiqiu; Gao, Chunlin; Xia, Zhengkun (Cellular and Molecular Biology, 2024)
Podocyte injury plays a vital role in focal segmental glomerulosclerosis (FSGS), and apoptosis is one of its mechanisms. The transient receptor potential channel 6 (TRPC6) is highly expressed in podocytes and mutations mediate podocyte injury. We found TRPC6 gene mutation (N110S) was a new mutation and pathogenic in the preliminary clinical work. The purpose of this study was to investigate the potential mechanism of mutation in TRPC6 (TRPC6-N110S) in the knock-in gene mouse model and in immortalized mouse podocytes (MPC5). Transmission electron microscopy was used to evaluate renal injury morphology. We measured 24-hour urinary albumin-to-creatinine ratios and major biochemical parameters such as serum albumin, urea nitrogen, and total cholesterol. The results of CCK-8 assay and apoptosis experiments showed that the TRPC6-N110S overexpression group had slower proliferative activity and increased apoptosis than the control group. FluO-3 assay revealed increased calcium influx in the TRPC6-N110S overexpression group. Podocin level was decreased in TRPC6-N110S group, while TRPC6 and desmin levels were increased in TRPC6-N110S group. The 24 h uACR at 6 weeks was significantly higher in the pure-zygotes group than in the WT and heterozygotes groups, and this difference was found at 8 and 10 weeks.TRPC6 levels showed no significant difference between homozygote and WT mice. Compared to homozygote group, expression of podocin and nephrin were increased in WT, but levels of desmin was decreased in WT. Our results suggest that this new mutation causes podocyte injury probably by enhancing calcium influx and podocyte apoptosis, accompanied by increased proteinuria and decreased expression of nephrin and podocin.